Four Dimensions of Women’s Empowerment in Tourism: Case Study of Indrayanti Beach, Yogyakarta, Indonesia - Wardhani, Arisanti Ayu; Susilowati, Indah (Universitas Muhammadiyah Yogyakarta, 2021)
The emergence of sustainable tourism has led to a new tourism concept called ecotourism. Ecotourism has the principle of environmental preservation and the local communities’ welfare produces a significant impact on indigenous people in the area. This is because the local community is involved in managing sustainable tourism. Women who are part of the community have the same opportunities as men in accessing opportunities from ecotourism activities. Based on empirical research results, tourism activities create alternative jobs for women to be more independent economically, including the fact that the participation of women in tourism activities has a positive impact on them socially. Empowering women is an important part of community welfare efforts in the scope of tourism, so that women’s empowerment is important in the tourism development process. This study aims to analyze the ongoing empowerment of women and what factors are the drivers and barriers to empowerment in Indrayanti Beach as one of the leading destinations in Gunungkidul Regency as seen from four dimensions (economic, social, political, and psychological). The mixed-method approach has been used in research. It was found that the level of women’s empowerment in Indrayanti Beach had shown a good enough score with the highest average score in the economic dimension, namely 7.64, where women economically have received a positive impact from Indrayanti Beach. The lowest average score is on the political dimension, with a value of 5.82. Women politically still do not have awareness if their role is important for the sustainability of Indrayanti Beach tourism. For the social dimension, the average is 6.81, and the psychological dimension on average is 7.47, where women feel socially and psychologically empowered quite well. The main driver of women’s empowerment is the opportunity and permission from their families to participate in tourism activities. The main obstacle to women’s empowerment is the low self-confidence due to skills that have not been maximized.